APLIKASI PENILAIAN KINERJA DOSEN MENGGUNAKAN METODE ADDITIVE RATIO ASSESSMENT ( ARAS ): Indonesia - khairunnisa, Baiq; Murniati, Wafiah; Hamdi, Saeful; Fadli, Sofiansyah (Universitas Majalengka, 2022)
STMIK Lombok is one of the Private Universities that regularly conduct assessments of lecturers every semester. This is done in order to motivate lecturers in improving service to students. Although in its implementation, the performance assessment of this lecturer runs smoothly but has not reached optimal because it still uses Microsoft Excel in the calculation process so it takes a long time in the process of calculating values and reporting process. so it still needs improvements, especially in the assessment process using the application. This research aims to build an assessment information system and evaluate the performance of STMIK Lombok lecturers. The ARAS (Additive Ratio Assessment) method is one of the multicryteria decision-making methods based on the concept of combat using a utility degree, namely by comparing the overall index value of each alternatife to the optimal alternative overall index value. This decision support system can provide selected alternative decisions that can later be used as a reference to determine the best Lecturer Performance. The system development method used is Waterfall, PHP as a programming language and uses data flow diagram (DFD) system modeling. The testing process used in this application is the Black Box. The results of this built Application can speed up the process of calculating the performance assessment of lecturers and the reporting process more effectively and efficiently.